Theorizing media, communication and social change: towards a processual approach. (May 2019) - Mihelj, Sabina; Stanyer, James
Debates about the role of media and communication in social change are central to our discipline, yet advances in this field are hampered by disciplinary fragmentation, a lack of shared conceptual language and limited understanding of long-term shifts in the field. To address this, we first develop a typology that distinguishes between approaches that foreground the role of media and communication as an agent of change, and approaches that treat media and communication as an environment for change. We then use this typology to identify key trends in the field since 1951, including the sharp downturn in work focusing on economic aspects of change after 1985, the decline of grand narratives of social change since 2000 and the parallel return to media effects. We conclude by outlining the key traits of a processual approach to social change, which has the capacity to offer the basis for shared language in the field. This language can enable us to think of media, communication and social change across its varied temporal and social planes, and link together the processes involved in the reproduction of status quo with fundamental changes to social order.